Evolução, conjuntura e perspectivas da hotelaria de Salvador/Ba: um estudo de competitividade e de desempenho - FIGUEIREDO, Mauro Lopes (2016)
The objective of this study is to investigate and analyze the structure and development of the hospitality industry of Salvador, capital of the Brazilian State of Bahia, between 2011 and 2015, in light of the Michael Porter’s industrial structural analysis. Firstly, a panorama of the evolution of hospitality business in Salvador was made, supported by the occupancy and average daily rates from the past 15 years, in comparison with the growth of tourism flow and increase of accommodations in Bahia State in the same period. In order to draw a more accurate comparison, a parallel between this evolution and other tourist Brazilian capitals was made. After building this scenario, a structural analysis of the sector was performed, an exploratory research based on the classic theoretical framework on competitive strategy, seeking secondary data so as to know the external influences upon the competitive forces, as described by Michael Porter. This research was complemented by a qualitative study by means of structured interviews with managers and professionals of the hospitality industry of Salvador. As a result, after studying and interpreting the forces, by the analysis of data obtained in the interviews, it was possible to identify a high degree of rivalry among competitors of this industry and a medium bargaining power of their suppliers. A low threat of substitute lodging services and a medium bargaining power of customers were observed. The insufficient tourist flow in Salvador was pointed out as the main entry barrier of new competitors. Afterward, the investments in marketing were verified, and a low economic-financial performance was observed in a significant portion of the researched hotels. On the other hand, a group of hotels was found to be having good results in the past few years. It was verified that there was no strong correlation between the investments made in the hospitality business in the past five years in Salvador as a consequence of the 2014 FIFA World Cup and 2016 Olympic Games, both of which were hosted by Brazil. And, lastly, some prospects were identified for the hospitality industry of Salvador, based on the perspective of hotel managers interviewed, considering a five-year horizon (2016-2020), which indicate a reduction in investments of more than half the hotels researched, negative evolution or low percentage of the gross profitable growth, downsizing the staff, no intention, for the most part, of building a new hotel in Salvador, as they believe the city does not admit new hotels due to the low demand for guests, to the high supply of hotels, to the unsatisfactory financial return, and to the deficient rate of return on the invested capital.